Neurodegenerative Disease: A Perspective on Cell-Based Therapy in the New Era of Cell-Free Nano-Therapy - M. Metcalfe, Su; Bickerton, Sean; Fahmy, Tarek (Current Pharmaceutical Design, 2017)
Neurodegenerative diseases (NDD) result in irreversible loss of neurons. Dementia develops when disease-induced neuronal loss becomes sufficient to impair both memory and cognitive functioning and, globally, dementia is increasing to epidemic proportions as populations age. In the current era of regenerative medicine intense activity is asking, can loss of endogenous neurons be compensated by replacement with exogenously derived cells that have either direct, or indirect, neurogenic capacity? But, more recently, excitement is growing around an emerging alternative to the cell-based approach - here nanotechnology for targeted delivery of growth factor aims to support and expand resident central nervous system (CNS) stem cells for endogenous repair. The concept of a high volume, off-the-shelf nano-therapeutic able to rejuvenate the endogenous neuroglia of the CNS is highly attractive, providing a simple solution to the complex challenges posed by cell-based regenerative medicine. The role of inflammation as an underlying driver of NDD is also considered where anti-inflammatory approaches are candidates for therapy. Indeed, cell-based therapy and/or nanotherapy may protect against inflammation to support both immune quiescence and neuronal survival in the CNS - key targets for treating NDD with the potential to reduce or even stop the cascading pathogenesis and disease progression, possibly promoting some repair where disease is treated early. By design, nanoparticles can be formulated to cross the blood brain barrier (BBB) enabling sustained delivery of neuro-protective agents for sufficient duration to reset neuro-immune homeostasis. Proven safe and efficacious, it is now urgent to deliver nano-medicine (NanoMed) as a scalable approach to treat NDD, where key stakeholders are the patients and the global economy.
Keywords: cell therapy